2012
DOI: 10.1063/1.3675278
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural characterization of thermal oxidation effects of erbium thin films deposited by electron beam on silicon

Abstract: Thermal oxidation effects on the structural, compositional, and optical properties of erbium films deposited on silicon via electron beam evaporation were analyzed by x-ray diffraction, x-ray photoelectron spectroscopy, Auger electron spectroscopy, and spectroscopic ellipsometry. A gradual rise in oxidation temperature from 700 to 900 °C resulted in a transition from ErO- to Er2O3-rich phase. Additional increase in oxidation temperature above 1000°C led to the formation of erbium silicate due to further oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…1S,d), using general Tauc model and assuming Er 2 O 3 films as allowed transitions indirect bandgap material similar to Ref. [13], showed that the annealing results in some decrease of bandgap value from E g = 5.28 eV (as-deposited films) down to E g = 4.95 eV (T A = 1100°C) ( Fig. 1S,d).…”
Section: Evolution Of Refractive Index and Film Thickness With T Asupporting
confidence: 60%
See 1 more Smart Citation
“…1S,d), using general Tauc model and assuming Er 2 O 3 films as allowed transitions indirect bandgap material similar to Ref. [13], showed that the annealing results in some decrease of bandgap value from E g = 5.28 eV (as-deposited films) down to E g = 4.95 eV (T A = 1100°C) ( Fig. 1S,d).…”
Section: Evolution Of Refractive Index and Film Thickness With T Asupporting
confidence: 60%
“…As-deposited films demonstrated the refractive index n = 1.85 9-1.861 (at 1.95 eV) similar to that reported for Er 2 O 3 in Refs. [12,13]. Thermal treatment results in its non-monotonic variation (Fig.…”
Section: Evolution Of Refractive Index and Film Thickness With T Amentioning
confidence: 99%
“…An examination of the S2p spectra was deemed necessary to understand how the reaction differed between both molecules. In most situations, interpreting S2p on silicon (111) substrate is challenging due to the satellite peaks induced from the nearby Si2s (~152 eV), which is a result of surface plasmon (silicon’s plasmon energy is ~17 eV) being excited by the photoelectrons [ 27 , 28 , 29 ]. Hence, obtaining a clean S2p peak is often difficult on silicon surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum PL intensity was obtained from the thin lm containing 12 at% of Er in the deposit. The higher Er 3+ concentrations may lead to the formation of micro-clusters of erbium silicates such as Er 2 SiO 5 48,49 or Er 2 Si 2 O 7 , 50,51 which are also luminescent in nature. However, it is observed that further increase in Er content than 12 at% results in the quenching of the PL emission.…”
Section: Optical Propertiesmentioning
confidence: 99%